Diagnosis, management and mortality in acute aortic syndrome: results of the Spanish Registry of Acute Aortic Syndrome (RESA-II). Issue 7 (1st October 2018) - Evangelista, Arturo; Rabasa, José Manuel; Mosquera, Victor X; Barros, Antonio; Fernández-Tarrio, Ruben; Calvo-Iglesias, Francisco; Ferrera, Carlos; Rozado, Jose; López-Ayerbe, Jordi; Garrote, Carmen; San román, Jose-Alberto; Nistal, Francisco; et al.
Abstract: Background: Recent advances in the diagnosis and treatment of acute aortic syndrome should improve the outcome of this disease. The Spanish Registry of Acute Aortic Syndrome aimed to assess current results in acute aortic syndrome management in a wide cohort of hospitals in the same geographical area. Methods: From January 2012 to January 2014, 26 tertiary hospitals included 629 consecutive patients with acute aortic syndrome: 73% men, mean age 64.7±14 years (range 22–92), 443 type A (70.4%) and 186 type B (29.6%). Results: Time elapsed between symptom onset and diagnosis was <12 hours in 70.7% of cases and <24 hours in 84.0% (median 5 hours; 25 th –75th percentiles, 2.7–15.5 hours). Computed tomography was the first diagnostic technique in 78% of patients and transthoracic echocardiography in 15%. Surgical treatment was indicated in 78.3% of type A acute aortic syndrome. The interval between diagnosis and surgery was 4.8 hours (quartile 1–3, 2.5–11.4 hours). Among the patients with type B acute aortic syndrome, treatment was medical in 116 cases (62.4%), endovascular in 61 (32.8%) and surgical in nine (4.8%). Type A mortality during hospitalisation was 25.1% in patients treated surgically and 68% in those treated medically. Mortality in type B was 13.8% in those with medical treatment, 18.0% with endovascular therapy and 33.0% with surgical treatment. Conclusion: Improvements in the diagnosis and treatment of acute aortic syndrome have not resulted in a significant reduction in hospital mortality. The results of this study reflect more overall and less selected information on acute aortic syndrome management and the need for sustained advances in the therapeutic strategy of acute aortic syndrome.